Reading between the signs : intercultural communication for sign language interpreters - Mindess, Anna. (Boston : Intercultural Press, A Nicholas Brealey Publishing Company, 2014)
"In Reading between the Signs, Anna Mindess provides a new perspective on a poorly understood culture, American Deaf culture. With the collaboration of three distinguished Deaf consultants, Mindess explores the implication of cultural differences at the intersection of the Deaf and hearing worlds. This new, third edition of her classic and best-selling text covers several new topics of great interest to activists and interpreters, including teaming with Deaf interpreters and cultivating a "Deaf heart." It is used in Deaf studies courses and interpreter training programs worldwide.Anna Mindess has been a Sign Language interpreter for more than thirty years. She lives in Berkeley, California. "--
"An essential and invaluable tool for sign language interpreters, students, and everyone wishing to understand American Deaf culture. Reading Between the Signs, Third Edition provides a new perspective on American Deaf culture. With collaboration of three distinguished Deaf consultants, Mindess explores the implications of cultural differences at the intersection of the Deaf and hearing worlds. Previous editions of Reading Between the Signs have been used in interpreter training programs worldwide. New material includes a section on legal interpreting and the emerging area of hearing interpreters teaming with Deaf interpreters"--
The study of culture -- Selected topics in intercultural communication -- Do Americans really have a culture? -- American deaf culture -- Multicultural deaf culture -- Culture, change, and technology -- The impact of cultural differences on interpreting situations -- Multicultural interpreting challenges -- The interpreter's role and responsibilities -- Techniques for cultural adjustments -- Interpreting in a virtual world -- Cultural sensitivity shouldn't end at five o'clock -- The road to the future is paved with respect for the past.
Includes bibliographical references and index.
Keywords: Interpreters for deaf people -- United States; Communication and culture -- United States; Intercultural communication -- United States; Deaf -- Means of communication -- United States; American Sign Language